PERANCANGAN WEBSITE LAPORAN DATA UMKM PROVINSI NUSA TENGGARA TIMUR MENGGUNAKAN JAVASCRIPT DAN NODE.JS - De Beny, Sandra; Yusuf, Muhammad Rafly (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2024)
Penelitian ini memiliki tujuan untuk merancang sebuah sistem berbasis website untuk pelaporan data Usaha Mikro, Kecil, dan Menengah (UMKM) di Provinsi Nusa Tenggara Timur (NTT). Teknologi yang digunakan dalam pengembangan website ini adalah Javascript dan Node.js untuk mendukung sisi frontend dan backend, dengan bantuan database server XAMPP. Proses pengembangan mengikuti metode waterfall, yang mencakup tahap analisis kebutuhan, desain, pengkodean, pengujian, dan pemeliharaan, yang dilakukan secara berurutan. Penelitian ini berfokus pada pengelolaan data laporan UMKM dari berbagai kabupaten di Provinsi NTT yang sebelumnya diinput secara manual. Sistem yang dirancang bertujuan untuk membantu Dinas Pariwisata dan Ekonomi Kreatif Provinsi NTT dalam mengatasi masalah ketidaklengkapan dan keterbatasan data UMKM. Hasil dari pengujian menunjukkan bahwa website pelaporan data UMKM ini dapat berjalan tanpa kendala teknis dan siap diimplementasikan oleh pemerintah setempat. Secara keseluruhan, implementasi teknologi Javascript dan Node.js terbukti berhasil dalam membangun dan merancang website yang dapat membantu pengelolaan data UMKM di Provinsi NTT.   This research aims to design a website-based system for the reporting of reporting data on Micro, Small and Medium Enterprises (MSMEs) in East Nusa Tenggara Province. East Nusa Tenggara (NTT) Province. The technology used in the development of this website development is Javascript and Node.js to support the frontend and backend, with the help of the XAMPP database server and backend, with the help of the XAMPP database server. The process of development process follows the waterfall method, which includes the stages of needs analysis, design, coding, and testing analysis, design, coding, testing, and maintenance stages, which are carried out sequentially sequentially. This research focuses on managing MSME report data report data from various districts in NTT Province which were previously inputted manually. The designed system aims to assist the Tourism and Creative Economy Office of NTT Province in overcoming the problem of Creative Economy of NTT Province in overcoming the problem of incomplete and limited MSME data. The results of the test show that the MSME data reporting website MSME data reporting website can run without technical problems and is ready to be implemented by the local government.local government. Overall, the implementation of Javascript and Node.js technology has proven to be success in building and designing a website that can help that can help manage MSME data in NTT Province.